How do you simplify #(-4h+2)(3h+7)#?

1 Answer
Dec 12, 2016

Answer:

#-12h^2-22h+14#

Explanation:

Simply distribute using the F.O.I.L method. See below:

#(-4h*3h)=-12h^2# and #(-4h*7)=-28h#

#(2*3h)=6h# and #(2*7)=14#

Now we have all four parts of the equation. See below:

#12h^2-28h+6h+14#

Since we have like-terms, #(-28h+6h)#, we need to add those together to get the simplified equation. #(-28h+6h)=-22h#

Now the equation reads:

#(-4h+2)(3h+7)=12h^2-22h+14#

Therefore the finalized simplified version of the equation is:

Answer: #12h^2-22h+14#